Optimalisasi Komunikasi Pemasaran dalam MeningkatkanBrand Awareness : Studi Kasus Whiz Hotel Cikini - Adinda, Karina; Priatna, Wahyu Budi (Universitas Islam Balitar, 2025)
The hospitality industry in Jakarta continues to grow amid increasing competition and digital advancements. In this context, brand awareness plays a vital role in a hotel’s competitiveness. This study analyzes the marketing communication strategy of Whiz Hotel Cikini in building brand awareness using the Hierarchy of Effects Model by Lavidge and Steiner, which illustrates the consumer process from awareness to decision. A descriptive qualitative method with a case study approach was used, based on observations of promotional activities from January to June 2025. Findings show that Instagram serves as the hotel’s primary promotional platform. Visually engaging content attracts attention, creates positive perception, and strengthens brand recall. The use of visual storytelling effectively builds emotional connections and enhances audience understanding of the hotel’s identity. Tailoring marketing communication to align with consumer psychological stages is key to establishing sustainable brand awareness.